Learning to be Lebanese: socializations of citizenship and subjecthood in Beiruti primary schools - Lansing, Jade (AUC Knowledge Fountain, 2014)
This research project will explore the ways the Lebanese state and individual classroom actors construct and contest citizenship through the curriculum and structure of civics classrooms in contemporary Lebanese primary schools. Using civics classrooms as a lens to understand broader trends in educational environments, this study will analyze the role of education in the narration, diffusion, and aggravation of social and political discord. It argues that schools and classrooms are not passive or neutral mirrors of external dynamics, but rather play an active role in the narration and construction of these realities. This research shows that education is a space dominated by conflicting interests, serving as both a source of control and individual empowerment. It is the great irony of citizenship that, the state apparatus, and the sectarian demarcations it reiterates in Lebanon, are reinforced by the very initiatives that seek to challenge these hegemonic and hierarchical structures by nature of their reliance on the state and sectarian affiliations as sources of change. This project aims to address this contradiction within the practice of civics education in Lebanese primary schools. Based on ethnographic fieldwork in Beiruti primary school classrooms as well as review of national legislation and educational administrative documents, this interdisciplinary study explores the relationship between national administrative reforms and everyday classroom practices. This analysis is situated within a broader interrogation of what civics classrooms teach young students about their rights and duties as Lebanese citizens, and how the content and implementation of civics education differs between schools. In addition to interviews and reviewing textbooks and educational administrative documents, I attended civics classes at three Beiruti elementary schools in order to observe grading methodology, group project dynamics, teaching styles, and students’ classroom engagement to understand how students become citizens within the school environment.